A conceptual framework to develop a patient-reported experience measure of the quality of mental health care: a qualitative study of the PREMIUM project in France. Issue 1 (1st January 2021) - Fernandes, S; Fond, G; Zendjidjian, X; Michel, P; Lançon, C; Berna, F; Schurhoff, F; Aouizerate, B; Henry, C; Etain, B; Samalin, L; Leboyer, M; et al.
ABSTRACT: Background : The objective of this study was to develop a conceptual framework to define a domain map describing the experience of patients with severe mental illnesses (SMIs) on the quality of mental health care. Methods : This study used an exploratory qualitative approach to examine the subjective experience of adult patients (18–65 years old) with SMIs, including schizophrenia (SZ), bipolar disorder (BD) and major depressive disorder (MDD). Participants were selected using a purposeful sampling method. Semistructured interviews were conducted with 37 psychiatric inpatients and outpatients recruited from the largest public hospital in southeastern France. Transcripts were subjected to an inductive analysis by using two complementary approaches (thematic analysis and computerized text analysis) to identify themes and subthemes. Results : Our analysis generated a conceptual model composed of 7 main themes, ranked from most important to least important as follows: interpersonal relationships, care environment, drug therapy, access and care coordination, respect and dignity, information and psychological care. The interpersonal relationships theme was divided into 3 subthemes: patient-staff relationships, relations with other patients and involvement of family and friends. All themes were spontaneously raised by respondents. Conclusion : This work provides a conceptual framework that will inform the subsequent development of a patient-reported experience measure to monitor and improve the performance of the mental health care system in France. The findings showed that patients with SMIs place an emphasis on the interpersonal component, which is one of the important predictors of therapeutic alliance. Trial registration : NCT02491866